Alien autopsy [videorecording (DVD)] - Campbell, Jonny; McPartlin, Anthony David, 1975-; Donnelly, Declan Joseph Oliver, 1975-; Pullman, Bill; Stanton, Harry Dean, 1926-2017 (Distributed by Warner Home Video, 2010)
A mysterious, intriguing and quirky film about two guys who believe they have film evidence about an alien cover up and government conspiracy regarding the famed Roswell incident. What ensues is nothing short of a rollercoaster ride for the two unlikely lads from London. Hurled into the heart of a media frenzy, the spotlight of the world focuses on them and with it the unwanted attention of the world's biggest super power.